2020
DOI: 10.1016/j.jcmgh.2019.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Flagellin-Specific Adaptive Immunity Reveals Links to Dysbiosis in Patients With Inflammatory Bowel Disease

Abstract: Analyses of memory immune responses in ulcerative colitis and Crohn's disease patients have shown reduced vaccine-specific responses and proportionally increased flagellin-specific responses compared with healthy controls. Flagellin-specific T cells may be a useful biomarker and provide insight into inflammatory bowel disease pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 44 publications
6
36
0
Order By: Relevance
“…Consistent with previous reports 2 , 3 , 4 of bacterial-specific T cells in IBD, Uchida et al 5 found that there was no difference between healthy controls and CD patients in the absolute number of circulating OmpC 321–340 –specific CD4 + T cells. In addition, as previously observed, 2 , 3 OmpC 321–340 –specific CD4 + T cells had a T-helper 17 cell phenotype, defined as CD161 + CXCR3 neg . After sorting and clonal expansion, tetramer + OmpC 321–340 –specific cells retained antigen specificity and, strikingly, clones from CD patients secreted significantly less interleukin (IL)10 than those from healthy controls.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous reports 2 , 3 , 4 of bacterial-specific T cells in IBD, Uchida et al 5 found that there was no difference between healthy controls and CD patients in the absolute number of circulating OmpC 321–340 –specific CD4 + T cells. In addition, as previously observed, 2 , 3 OmpC 321–340 –specific CD4 + T cells had a T-helper 17 cell phenotype, defined as CD161 + CXCR3 neg . After sorting and clonal expansion, tetramer + OmpC 321–340 –specific cells retained antigen specificity and, strikingly, clones from CD patients secreted significantly less interleukin (IL)10 than those from healthy controls.…”
supporting
confidence: 90%
“…In support of the concept that bacterial antigens drive IBD, there are associations between the frequency and phenotype of bacterial-specific CD4 + T cells and IBD disease severity. 2 , 3 , 4 However, a limitation of these studies was that specific epitopes were not mapped, meaning that it was not possible to create tetramer reagents, mainstay reagents in the immunology tool box, which allow precise quantification and phenotypic characterization of antigen-specific T cells.…”
mentioning
confidence: 99%
“…Indeed, intestinal microbiota-specific memory CD4 + T cells are abundant in the peripheral blood [ 17 ]. Importantly, blood circulation of microbial protein-specific T cells increases upon induction of gut dysbiosis-mediated intestinal inflammation [ 16 ]. If colonization of gut bacteria expressing an MBP mimotope is elevated, an increase in blood circulating MBP mimotope-reactive T cells and MBP mimotope + DCs may increase the risk of MS.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, gut bacteria-specific T cells may migrate into the blood circulation. Indeed, gut microbiota-specific T cells are detected in the blood of IBD patients [ 16 ]. Even in healthy individuals, gut microbiota-reactive T cells can be detected in the blood [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial flagellin derived from CBir1 is a dominant target of pathologic Abs in CD patients, 91,92 but the role of flagellin‐specific CD4 + T cells role in pathogenesis was poorly studied until recently. Cook and colleagues found that both CD and UC patients have an increase in A4‐Fla2 (closely related to CBir1) specific CD4 + T cells, and these changes may be driven from intestinal microbiome alterations 93 …”
Section: T Cell Interactions With Organoids—talking Is Essential To Amentioning
confidence: 99%